Subthreshold Diode Micropulse Laser (SDM) for Persistent Macular Thickening and Limited Visual Acuity After Epiretinal Membrane Peeling - Luttrull JK (Dove Medical Press, 2020)
Jeffrey K Luttrull Private Practice, Ventura County Retina Vitreous Medical Group, Ventura, CA 93003, USACorrespondence: Jeffrey K Luttrull 3160 Telegraph Road, Suite 230, Ventura, California 93003, USATel/Fax +1 805-650-0865Email jkluttrull@gmail.comPurpose: To examine the effect of low-intensity/high-density subthreshold diode micropulse laser (SDM) on visual acuity (VA) and macular thickness in eyes with limited visual recovery and persistent macular thickening after epiretinal membrane peeling.Methods: A retrospective review of medical records identified all patients undergoing SDM after membrane peeling in a clinical vitreoretinal subspecialty practice. Exclusion criteria included other obfuscating ocular disease or loss to follow-up after SDM treatment.Results: All 19 eyes of 18 patients identified were included for study. After membrane peeling, VA improved from an avg. Snellen 20/240 [logMAR 1.08] to 20/72 [0.56] (p=0.0004). Attributed to persistent macular thickening following membrane peeling, overall VAs then gradually declined to an avg. of 20/91 [0.66] by 4− 109 months (avg. 41) post vitrectomy, at which point panmacular SDM was performed. An avg. 15 months post SDM, both VA (to avg. 20/68 [0.53]) and maximum macular thickness improved (p=0.007 and p=0.008, respectively). There were no adverse treatment effects.Conclusion: Low-intensity/high-density subthreshold (sublethal) diode micropulse laser (SDM) may reduce macular thickening and improve visual in eyes with persistent macular thickening after membrane peeling even years after vitrectomy.Keywords: laser, micropulse, subthreshold, epiretinal membrane, macular thickening, macular edema, reset, heat-shock proteins